Microstructural investigation of D2 tool steel during rapid solidification - Khatibi, P. Delshad; Phillion, A.B.; Henein, H. (Taylor and Francis, 2013)
Rapid solidification yields significant enhancement in mechanical properties through reduced microsegregation and the formation of metastable phases. Impulse Atomization (IA) in helium and nitrogen and Water Atomization (WA) have been utilized to produce powders of D2 tool steel of different sizes from 90-1000 μm. SEM analysis was carried out to characterize the effect of particle size and cooling gas on the microstructure. It was determined that higher cooling rates result in smaller 2 and a lower percentage of eutectic. SEM image analysis along with coarsening model were used to predict eutectic and primary phase undercooling of different particles. Small particles exhibited a higher amount of undercooling (both primary phase and eutectic undercooling). The particles exposed to a He atmosphere during atomization had a larger amount of eutectic undercooling whereas the nitrogen-cooled samples had larger dendrite spacing. The fraction of primary phase that solidified during the recalescence was then calculated based on the amount of primary phase undercooling under adiabatic conditions. In smaller particles, it was found that there was a larger amount of primary phase solidified during recalescence due to a higher amount of primary undercooling. Based on primary phase undercooling values, critical nuclei radius of austenite and assuming homogenous nucleation the number of austenite unit cells in the stable nucleus was calculated.